2020
DOI: 10.1177/0022219420917338
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Classified With Specific Language Impairment Have a Learning Disability in Writing? A Meta-Analysis

Abstract: In this meta-analysis, we examined whether children classified with specific language impairment (SLI) experience difficulties with writing. We included studies comparing children with SLI to (a) typically developing peers matched on age ( k = 39 studies) and (b) typically developing younger peers with similar language capabilities ( k = six studies). Children classified with SLI scored lower on writing measures than their typically developing peers matched on age ( g = −0.97) when all writing scores in a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 70 publications
6
27
1
5
Order By: Relevance
“…In line with this research, a recent meta-analysis (Graham, Hebert, Fishman, Ray, & Rouse, 2020) showed a consistent and significant association between oral and written language problems from the preschool years to adolescence (Grade 12). According to the authors, three theoretical explanations can be given for the link between oral language and writing difficulties.…”
Section: The Role Of Oral Language and Text Generation Skills In Writsupporting
confidence: 73%
“…In line with this research, a recent meta-analysis (Graham, Hebert, Fishman, Ray, & Rouse, 2020) showed a consistent and significant association between oral and written language problems from the preschool years to adolescence (Grade 12). According to the authors, three theoretical explanations can be given for the link between oral language and writing difficulties.…”
Section: The Role Of Oral Language and Text Generation Skills In Writsupporting
confidence: 73%
“…Instead, composites appear to be created based on their academic domain. While there is intuitive logic to such a structure, it is also possible that the latent structure of the battery is influenced by other shared abilities, such as students' functioning at various levels of language, a concept that predicts the cross‐domain deficits often found in students with reading and language disorders (Coleman et al, 2009; Graham et al, 2020; Snowling et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ehri, 2000). Indeed, students with dyslexia often demonstrate spelling problems (Coleman et al, 2009), and students with oral language impairment display challenges with written composition and reading comprehension (Graham et al, 2020; Snowling et al, 2020). In the KTEA‐3 manual factor analysis, subtest variance unexplained by academic domain continued to demonstrate an association with other subtests at a common level of language (Kaufman & Kaufman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By corollary oral language at word, sentence and text level supports text generation (Abbott & Berninger, 1993;Babayiğit & Stainthorp, 2010;Kim, Al Otaiba, Folsom, Greulich, & Puranik, 2014;Olinghouse & Leaird, 2009;Savage, Kozakewich, Genesee, Erdos, & Haigh, 2017;Sénéchal, Hill, & Malette, 2018). The importance of oral language in supporting written text production is evident by the significant difficulties in writing experienced by children with language problems (for review see Graham, Hebert, Fishman, Ray, & Rouse, 2020).…”
Section: Writing Developmentmentioning
confidence: 99%
“…Poor readers with a reasonable level of listening comprehension seem to have responded better to the intervention on the sentence combining measure while those with poor oral language skills may be resistant to intervention (Al Otaiba & Fuchs, 2002). Those with poor oral language skills experience difficulties with both wordand sentence-level skills (Graham et al, 2020) and this may explain their resistance to intervention as compared to poor readers. Reading skills are thus important for the initial response to the sentence combining intervention, and there was, in fact, some small gains to reading decoding made by participants perhaps as a side effect of the reading exposure undertaken during the intervention.…”
Section: Exploring the Roles Of Oral Language And Readingmentioning
confidence: 99%